Pengaruh E-Service Quality Terhadap E-Customer Loyalty Pada Personal Shopper Dengan E-Customer Satisfaction Sebagai Variabel Intervening - Harjanti, Dhyah; Noerchoidah, Noerchoidah; Sahetapy, Wilma Laura; Marchyta , Nony Kezia; Han, David Christian (Majalah Ekonomi, 2026)
Changes in consumer behavior in shopping, especially online, triggered by the Covid-19 pandemic in Indonesia, have prompted one shopping center to innovate and adapt. One of the shopping center's efforts is to launch a personal shopper application to remain competitive during the pandemic. This study aims to analyze the effect of e-service quality and e-customer satisfaction as intervening variables on e-customer loyalty in personal shopper application services. The research method is a quantitative approach, with a survey of 256 respondents who have shopped through a personal shopper application in the last 3 months. Data processing was performed using SmartPLS version 4.0. The results showed that e-service quality had a positive and significant effect on e-customer satisfaction; e-service quality also had a positive and significant effect on e-customer loyalty; e-customer satisfaction had a positive and significant effect on e-customer loyalty; and e-customer satisfaction was proven to be an intervening variable in the relationship between e-service quality and e-customer loyalty.